FRI0046 Characterization of nitrotyrosine as a clinical biomarker for arthritis and joint injury. (23rd January 2014) - Misko, T.P.; Radabaugh, M.R.; Highkin, M.; Abrams, M.; Listello, J.; Friese, O.; Gallavan, R.; Bramson, C.; Hellio le Graverand-Gastineau, M.P.; Lohmander, L.S.; Roman, D.
Abstract : Background: Increased nitric oxide synthase (NOS) activity has been linked to joint injury and is associated with increased chondrocyte apoptosis, increased matrix metalloproteinase (MMP) activity, and decreased extracellular matrix synthesis. Osteoarthritis (OA) and rheumatoid arthritis (RA) show increased synovial tissue staining for both inducible NOS (iNOS) and its downstream product, nitrotyrosine (NT). Objectives: To characterize the utility of NT as a clinical biomarker for arthritis and joint injury. Methods: Biological fluids (synovial fluid [SF], plasma, urine) were analyzed from 3 patient cohorts and compared with aged-matched healthy volunteers (HV) (1): early-to-moderate OA (Kellgren & Lawrence Grades 2/3); (2): knee OA, RA, anterior cruciate ligament (ACL) injury, pseudogout; (3) RA treated with anti-TNF biotherapeutics for 6 months. Total concentrations of NT (protein-bound and free) and other MMPs, cytokines, or chemokines (MMP-3, interferon γ-induced protein 10 [IP-10], C-reactive protein [CRP]), were quantified by immunoassay. Cohort (3) plasma NT levels were correlated with the Disease Activity Score of 28 Joints (DAS28) and tender joint count before and after anti-TNF therapy. With plasma NT, demographic variables (age, gender, alcohol consumption, smoking history, and hormonal status) were used in regression analyses to predict DAS28. Data are presented as mean [95% CI]. Results: Plasma NT was increased in OA patients (n=143) compared with HV (n=174) (1250 [1116, 1383] pg/mL vs. 976.6 [893.1, 1060] pg/mL; P <0.0005, unpaired t test) while urinary NT was unchanged. SF-NT from patients with OA (n=115; 1377 [1047, 1708] pg/mL), ACL (n=206; 3150 [2815, 3485] pg/mL), or pseudogout (n=31; 5298 [3616, 6981] pg/mL) showed increased NT vs. non-arthritis controls (n=46; 693.2 [359.1, 1027]pg/mL; P <0.001, one-way ANOVA). In matched samples from the same subject, SF to plasma NT ratios were elevated in late-stage OA patients (prior to knee replacement surgery; n=40) vs. HV (n=37) (1.45 vs. 0.97; P =0.0047, unpaired t test). Plasma NT decreased from baseline in RA patients following 6-months of anti-TNF treatment (3774 [2711, 4838] pg/mL vs. 2374 [2014, 2734] pg/mL; P <0.05 one-way ANOVA). For every 1.1% change in log10 NT there was a 1.0% change in the log10 DAS28. Using NT as a key disease parameter, a statistical model defining a linear relationship between predicted and observed change in DAS28 was constructed after 6-months of therapy (R 2 =0.944). Prior to initiation of anti-TNF therapy, plasma NT in RA patients was positively correlated with CRP (n=18; Spearman coefficient: 0.655; P =0.0032), MMP-3 (0.593; P =0.0094), and IP-10 (0.492; P =0.0383) but negatively correlated with tender joint count (–0.479; P =0.0443). Conclusions: NT was found to be a clinical biomarker for arthritis and joint injury. NT not only correlates with key plasma biomarkers in arthritis patients, but also with clinical assessments of disease activity. Importantly, NT levels decreased in RA patients following anti-TNF therapy. NT may be a suitable biomarker for assessment of patient response to disease-modifying arthritis treatment. Disclosure of Interest: T. Misko Employee of: Pfizer Inc (at the time of the study), M. Radabaugh Employee of: Pfizer Inc (at the time of the study), M. Highkin Employee of: Pfizer Inc (at the time of the study), M. Abrams Employee of: Pfizer Inc (at the time of the study), J. Listello Employee of: Pfizer Inc (at the time of the study), O. Friese Employee of: Pfizer Inc, R. Gallavan Employee of: Pfizer Inc (at the time of the study), C. Bramson Employee of: Pfizer Inc, M. P. Hellio le Graverand-Gastineau Employee of: Pfizer Inc, L. S. Lohmander: None Declared, D. Roman Employee of: Pfizer Inc (at the time of the study)